An in silico comparative genomic report on transcription factors in three Arabidopsis species - Jazayeri, Seyed Mehdi (2018)
Transcription factors (TF) are the elements, which regulate gene expression. Regulatory function of TFs play an important role in plant biological processes and mechanisms. They may interconnect with other transcription factors or functional genes to modulate their expression in response to an internal/external factor like life cycle stage, growth, development and stress. Arabidopsis is the well-known and the most used model organism. Transcription factors of three Arabidopsis species including A. halleri, A. lyrata and A. thaliana, were compared. basic/helix-loop-helix (bHLH) with 220 TFs was the most abundant family among three Arabidopsis species while MYB and MYB related families considering as a whole group were more than bHLH with 308 TFs. No STERILE APETALA (SAP) TF homolog was found for A.halleri.  The common transcription factors among three species were 4,172 grouped in 1,212 clusters. The species-specific clustered TFs were 12, 30 and 58 for A. halleri, A. lyrata and A. thaliana respectively. Eight hundred ninety two single-copy gene clusters those have one gene copy from each species, i.e. 2,676 genes, were listed. Four hundred forty five TF singletons were not clustered and are unique among three species. For clustered TF belonging to each species, GO terms and SwissProt hits showed that A. halleri has two species-specific TFs involved in heavy metal response including Zinc finger protein AZF2 and two-component response regulator ARR11 while for A. lyrata specific TFs are involved in stress response and plant development. A. thaliana specific clustered TFs work on plant flower development and acclimation.